Comparative Efficacy of Prophylactic Bolus Phenylephrine versus Ephedrine on Maternal Hemodynamics and Neonatal APGAR Scores in Elective Cesarean Section: A Randomized Controlled Trial - Pande Made Praskita Putra Soma; Ruddi Hartono; Isngadi (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Spinal anesthesia-induced hypotension is a pervasive physiological challenge during cesarean delivery, precipitating maternal hemodynamic instability and compromising uteroplacental perfusion. While phenylephrine and ephedrine are the mainstay vasopressors for prophylaxis, their comparative impact on immediate neonatal vitality in the context of bolus administration remains a critical subject of investigation, particularly in resource-limited settings where infusion pumps are not universally available. This study aimed to rigorously compare the efficacy of prophylactic intravenous bolus phenylephrine versus ephedrine regarding maternal blood pressure control and neonatal APGAR scores. Methods: We conducted a prospective, randomized, double-blind experimental study at Dr. Saiful Anwar Regional General Hospital, Malang. Forty-two parturients classified as ASA I or II undergoing elective cesarean section were randomized into two groups. Immediately following subarachnoid block, Group P received a bolus of Phenylephrine (125 µg), and Group E received Ephedrine (10 mg). Hemodynamic parameters were recorded at baseline and at 1, 3, 6, 9, 12, 15, and 18 minutes post-anesthesia. The primary outcome was the neonatal APGAR score at the first minute. Results: Both vasopressor regimens successfully mitigated severe spinal-induced hypotension. There were no statistically significant differences in the magnitude of systolic or diastolic blood pressure reduction between the Phenylephrine and Ephedrine groups at any observed time point (p>0.05). However, a significant divergence was observed in neonatal outcomes. The mean first-minute APGAR score in the Phenylephrine group was significantly higher (7.62 ± 0.97) compared to the Ephedrine group (7.05 ± 0.74) with a p-value of 0.038. Conclusion: Phenylephrine and ephedrine demonstrated equipotent efficacy in maintaining maternal hemodynamic stability when administered as prophylactic boluses. However, phenylephrine prophylaxis resulted in superior immediate neonatal vitality as evidenced by significantly higher first-minute APGAR scores. Phenylephrine should be prioritized as the vasopressor of choice to optimize neonatal safety during cesarean delivery.